Analysis of Financial Technology Adoption in Savings and Loan Cooperatives: A UTAUT Approach among Millennials - Amos, Viktor; Papalangi, Nataniel (Eastasouth Institute, 2025)
Digital transformation has driven credit unions to adopt application-based financial technology (fintech) services to enhance accessibility and efficiency. However, adoption rates among millennials—a generation considered digital natives—remain varied, indicating the presence of unique factors influencing their acceptance of such technology. This study aims to analyze the influence of factors within the Unified Theory of Acceptance and Use of Technology (UTAUT) model, including performance expectancy, effort expectancy, social influence, and facilitating conditions, on the intention to use fintech applications among millennials. The research was conducted among members of Credit Union (CU) Mekar Kasih, a savings and loan cooperative that has implemented a digital system through the Escete application. Data were collected through a survey of 100 millennial respondents (aged 25–40) who are active users of the application. Using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach, the findings reveal that performance expectancy and facilitating conditions significantly influence usage intention, indicating that millennials are motivated by functional benefits and infrastructural support. Conversely, social influence and effort expectancy were found to be insignificant, suggesting that social pressure and perceived ease of use are not primary drivers of adoption in this context. These findings offer practical implications for cooperative managers and fintech developers to focus more on enhancing value-added features and strengthening supporting infrastructure rather than relying on social factors or interface simplicity.